2021
DOI: 10.1371/journal.pone.0253597
|View full text |Cite
|
Sign up to set email alerts
|

Is biological larviciding against malaria a starting point for integrated multi-disease control? Observations from a cluster randomized trial in rural Burkina Faso

Abstract: Objectives To evaluate the impact of anti-malaria biological larviciding with Bacillus thuringiensis israelensis on non-primary target mosquito species in a rural African setting. Methods A total of 127 villages were distributed in three study arms, each with different larviciding options in public spaces: i) no treatment, ii) full or iii) guided intervention. Geographically close villages were grouped in clusters to avoid contamination between treated and untreated villages. Adult mosquitoes were captured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The larval control trial was associated with 36% reduction of adult Culex mosquito densities. Similar reductions have been reported previously in Burkina Faso and Tanzania ( Geissbühler et al, 2009 ; Dambach et al, 2021 ). The low reduction rate compared to anophelines ( Antonio-Nkondjio et al, 2021 ) could be associated to the complex ecology of Culex mosquitoes in urban settings.…”
Section: Discussionsupporting
confidence: 91%
“…The larval control trial was associated with 36% reduction of adult Culex mosquito densities. Similar reductions have been reported previously in Burkina Faso and Tanzania ( Geissbühler et al, 2009 ; Dambach et al, 2021 ). The low reduction rate compared to anophelines ( Antonio-Nkondjio et al, 2021 ) could be associated to the complex ecology of Culex mosquitoes in urban settings.…”
Section: Discussionsupporting
confidence: 91%
“…The larval control trial was associated with 36% reduction of adult Culex mosquito densities. Similar reductions have been reported previously in Burkina Faso and Tanzania [27,28]. The low reduction rate compared to anophelines [20] could be associated to the complex ecology of Culex mosquitoes in urban settings.…”
Section: Discussionsupporting
confidence: 82%
“…The larviciding trial with VectorMax® G conducted in Yaoundé, Cameroon found out an impact both on malaria vectors and culex mosquitoes with reduction of 69% and 36.6% in aquatic habitats and adult density inside houses for culex species, respectively (Talipouo et al, 2023). The impact on other mosquito species such as Aedes spp and Culex mosquitoes was also found to be limited in some settings (Dambach et al, 2021). The timing of larviciding, exhaustive and accurate geo-locations and types of mosquito habitats were the primary hindrances to optimize the impact of LSM, and thus requiring the new technologies (Hardy et al, 2017(Hardy et al, & 2023.…”
Section: Discussionmentioning
confidence: 99%